Optimization of thermoelectric performance of SrSi2-based alloys via the modification in band structure and phonon-point-defect scattering - Kuo, Yung-Kang; Ramachandran, Balakrishnan; Lue, Chin-Shan (Frontiers in Chemistry, 2014)
Thermoelectric properties of alkaline-earth-metal disilicides are strongly dependent on their electronic band structure in the vicinity of the Fermi level. In particular, the strontium disilicide, SrSi2 with a narrow band gap of about few tens of meV is composed of non-toxic, naturally abundant elements, and its thermoelectric properties are very sensitive to the substitution/alloying with third elements. In this article, we summarize the thermoelectric performance of substituted and Sr-deficient/Sr-rich SrSi2 alloys to realize the high thermoelectric figure-of-merit (ZT) for practical applications in the electronic and thermoelectric aspects, and also to explore the alternative routes to further improve its ZT value.